2009
DOI: 10.1210/en.2009-0395
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Receptor Substrate-2 in β-Cells Decreases Diabetes in Nonobese Diabetic Mice

Abstract: Insulin receptor substrate-2 (Irs2) integrates insulin-like signals with glucose and cAMP agonists to regulate beta-cell growth, function, and survival. This study investigated whether increased Irs2 concentration in beta-cells could reduce beta-cell destruction and the incidence of type 1 diabetes in nonobese diabetic (NOD) mice. NOD mice were intercrossed with C57BL/6 mice overexpressing Irs2 specifically in beta-cells to create NOD(Irs2) mice. After backcrossing NOD(Irs2) mice for 12 generations, glucose ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…No spontaneous reversal to less than 11.11 mmol/l was observed in any of the control groups (n = 15 per group). Consistent with results reported by others (26,27), we found that 80% of female NOD mice on a regular diet devel-IL-10 (21). The intervention of dysregulated Th cells is therefore critical to stopping autoimmune progression and the inflammatory attack against β cells.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…No spontaneous reversal to less than 11.11 mmol/l was observed in any of the control groups (n = 15 per group). Consistent with results reported by others (26,27), we found that 80% of female NOD mice on a regular diet devel-IL-10 (21). The intervention of dysregulated Th cells is therefore critical to stopping autoimmune progression and the inflammatory attack against β cells.…”
Section: Resultssupporting
confidence: 92%
“…injection of regular human insulin (0.8 U/kg; Novo Nordisk) diluted in sterile saline. Blood glucose levels were measured before insulin administration and then every 15 minutes afterwards, for 60 minutes (26). Histological studies and insulitis scoring.…”
Section: Discussionmentioning
confidence: 99%
“…STZ can cause irreversible damage to pancreatic islet β-cells, inducing insulin secretion disorders, and resulting in the occurrence of diabetes [16]. The pictures in Figure 8 show that positive immunohistochemical staining was characterized by a deep tan in the pancreas; the positive parts mainly lying in the insulin-producing islet β-cells and the nuclei dyed blue.…”
Section: Resultsmentioning
confidence: 99%
“…Exendin-4 operates via Akt/Irs2 and mammalian target of rapamycin (31)(32)(33)(34), signaling components that in NSCs lead to Hes3 induction (10).…”
Section: Min6 Cells Cultured In DC Respond To Pharmacological Stimulamentioning
confidence: 99%